Key Determinants of Learning Analytics Adoption in Moroccan Universities - Zine, Abdelkhalek; Kaaouachi, Abdelali (Journal of Ecohumanism, 2024)
The adoption of learning analytics (LA) in Moroccan higher education is crucial for enhancing teaching processes in the country. This article examines the key factors influencing this adoption based on existing literature and a quantitative survey. A quantitative study is proposed to explore these factors, involving a sample of 150 teachers from specific universities who have already used LA or LMS. Data will be collected through a questionnaire designed to assess teachers’ familiarity with LA, their current usage, perceived benefits, and encountered obstacles. Data analysis, through structural equations, reveals several findings. The relationship between "Aligned Activities" and "LA Adoption" tends to be significant, as well as the impact of "Skills" on this adoption. However, the relationship between "LA Applications" and "LA Usage" is non-significant. These results shed light on the key factors of LA adoption in Moroccan higher education, providing guidance for effective integration of this technology.